Effect of sporophytic heterozygosity on the male gametophyte of the tetraploid potato (Solanum tuberosum) - Ortíz, R.; Peloquin, S. (Oxford University Press, 1994)
Quantitative variation for pollen stainability was examined in both tetraploid × diploid and tetraploid × tetraploid families of potato (Solanum tuberosum L.). The diploid parents, which were highly heterozygous, produced first division restitution (FDR) 2n pollen. The families used were not affected by cytoplasmic-genetic male sterility. Significant differences between families were found. FDR 2n pollen producing diploid clones had progenies with a significantly higher pollen stainability than those derived from crosses between tetraploid parents. This was related to the level of heterozygosity in the sporophyte. In FDR 2n pollen, 80% of the heterozygosity and a large fraction of epistasis present in the diploid parent was transmitted to its tetraploid progeny. This is important for the production of open pollinated, true potato seed, because pollen stainability is significantly correlated with fruit set (r = 0·85).Copyright 1994, 1999 Academic Press.